answersLogoWhite

0


Best Answer

3x+12=x+48: 3x-x=-12+48

2x=36

x=18

User Avatar

Wiki User

โˆ™ 2010-04-13 07:37:08
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.8
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1775 Reviews
More answers
User Avatar

lenpollock

Lvl 12
โˆ™ 2022-08-31 17:05:38

3x + 12 = x + 48

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: 3x plus 12 equals x plus 48?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

3x plus 5y equals 48 -3x plus 5y equals 12Solve the system of equations Enter your answer as an ordered pair?

3x+5y=48 5y=48-3x-3x+5y=12 -3x+(48-3x)=12-6x=-36x=65y=48-3(6)5y=30y=6(6,6)


3x plus 10x-48 equals 0?

3x + 10x - 48 = 0 13x = 48 x = 3.692307692


What is the answer to 3x equals 48?

x = 16 3x = 48 divide both sides by three to get x by itself x=16


What is 36 inches plus 12 equals?

36 + 12 = 48


How do you solve 3x squared plus 24x plus 48 equals 0?

The terms in x in the factorisation must be 3 and 1, the whole numbers must be factors of 48 ie 1/48, 2/24, 3/16, 4/12, or 6/8. The only ones which can combine with the 3 to give a sum of 24 are 4 and 12 viz: (3x + 12)(x + 4)


What is the foiled version of 3x2 - 24x plus 48?

(3x-12)(x-4)


What is 12 plus 12 plus 12 plus 12 equals?

12 + 12 = 24. 24+12=32. 32 + 12 = 44


What is the solution set of 3X-5 equals 48?

3x - 5 = 48 So 3x = 53 and x = 53/3 = 17.66...


What is the answer for 3x plus 6 equals 54?

This is elementary stuff: 3x + 6 = 54 Subtract 6 from each side: 3x = 48 Divide each side by 3: x = 16.


48 plus 48 plus 48 equals?

144


Solve -3x plus 4y equals 12?

-3x + 4y = 12 Temporary value of y: 4y = 3x + 12 y = (3x + 12) / 4 Substituting y: -3x + 4 [(3x+12) / 4] = 12 -3x + 12x + 48 = 12 -3x + 12x = 12 - 48 9x = 12 - 48 9x = -36 x = -36 / 9 x = -4 Subtituting x to get the final value of y: -3(-4) + 4y = 12 12 + 4y = 12 4y = 12 - 12 4y = 0 y = 0 Final answer: x = -4 y = 0 Check: -3x + 4y = 12 -3(-4) + 4(0) = 12 12 + 0 = 12 12 = 12 Solution 2: -3x + 4y = 12 Temporay value of x: 3x = 4y - 12 x = (4y - 12) / 3 Substituting x to get the value of y: 3[(4y - 12) / 3] + 4y = 12 12y - 36 + 4y = 12 16y = 12 + 36 16y = 48 y = 48 / 16 y = 3 Substituting y to get the value of x: -3x + 4(3) = 12 -3x + 12 = 12 -3x = 12 - 12 x = 0 Final Answer: x = 0 y = 3 Check: -3(0) + 4(3) = 12 12 = 12


What is 5x plus 48 plus 7x equals 12 x plus 4?

many solutions

People also asked